Determinação de Cd, Cu, Ni, Pb e Zn em águas marinhas oriundas da Bacia Potiguar utilizando a técnica de difusão em filmes finos por gradiente de concentração (DGT) - Pescim, Guilherme Favoreto [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The DGT technique has been used to determine and better understand the dynamics and bioavailability of metals in the sea near to marine outfalls. In this work, the DGT was assessed for the determination of Cd, Pb, Cu, Zn and Ni in marine water samples from Potiguar Basin in its conventional aspect (binding agent, Chelex-100 and diffusive agent: Diffusive polyacrylamide gel (D) and restrictive (R)) and determination of Pb and Cd through its alternative aspect (binding agent: Saccharomyces cerevisiae immobilized in agarose gels and diffusive agent: 3MM Chromatography Paper). The deployment curves for long periods of immersion in the sample, showed a good linear correlation for the conventional aspect to Zn (D: R²=0.9586, R: R²=0.9444), Ni (D: R²=0.9789, R: R²=0.9286) and Cu (D: R²=0.764, R: R²=0.8143), and alternative to Pb (R²=0.9228) and Cd (R²=0.9673). The results of the organic and inorganic composition analysis in conventional aspect, showed that for every element there is no significant fraction of organic compounds in the sample. In addition, considering the alternative aspect, the comparison of obtained and expected masses suggests that some of the Pb is not labile and that the main retention mechanism of Pb for S. Cerevisiae occurs through ion exchange

A técnica DGT tem sido utilizada para determinação e melhor compreensão da dinâmica e biodisponibilidade de metais em águas marinhas sujeitas a emissários. Neste trabalho, a DGT foi avaliada para a determinação de Pb, Cd, Cu, Zn e Ni em amostras de água marinhas da Bacia Potiguar na sua vertente convencional (agente ligante: Chelex-100 e agente difusivo: Gel de Poliacrilamida Difusivo (D) e Restritivo (R)) e determinação de Pb e Cd através de sua vertente alternativa (agente ligante: Saccharomyces cerevisiae imobilizada em géis de agarose e agente difusivo: Papel Cromatográfico 3MM). As curvas de imersão para longos períodos na amostra apresentaram boa correlação linear na vertente convencional para Zn (D: R²=0,9586; R: R²=0,9444), Ni (D: R²=0,9789; R: R² = 0,9286) e Cu (D: R²=0,764; R: R² = 0,8143), e alternativa para Pb (R2=0.9228) e Cd (R2=0.9673). Os resultados da análise da composição orgânica e inorgânica na vertente convencional, demonstraram que para todos os elementos não há fração significativa de compostos orgânicos na amostra. Além disso, para vertente alternativa, a comparação das massas obtidas e esperadas sugerem que parte do Pb não encontra-se lábil e que o principal mecanismo de sua retenção pela S. Cerevisiae ocorre através de troca iônica
Keywords: Agua - Composição; Difusão